Kulturformidlingens transformation - folkebibliotekernes formidling i en digital tid - Skøtt, Bo (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
The aim of this article is to investigate how the digital conversion that currently takes place in public libraries in Denmark, affects the perception of those cultural dissemination activities that result from the work with documents. My starting point is that the digital conversion means an increase in digital documents and that the characteristics of these documents differ so significantly from analog documents that it potentially means changes in both the practical handling and the conceptual universe associated with the designation, identification, and definition of practice. The study is conducted as a literature survey, where Johan Fjord Jensen (1988), Dag Solhjell (2001) and Jens Gudiksen (2005) constitute the theoretical framework and where eight public libraries’ digital strategies from region Midtjylland are analyzed on the basis of a heuristic approach to the discourse concept. The conclusion is that the eight digital strategies do not explicitly refer to concepts that traditionally denote the cultural activities of the public library (e.g. 'enlightenment' and 'cultural activity') but that these concepts are thematized and understood in new and more transmissive terms such as 'accessibility' 'usage frequency' and as 'need', 'consumption' and 'demand'. This happens because the eight strategies consider technology and the use of technology superior to content, which makes the strategies more part of the public libraries' legitimization work and less a part of the facilitation of people’s common actions in late modernity.